Pembuatan Biodiesel Dari Minyak Biji Kapuk (Ceiba Pentandra) Dengan Katalis Lempung Teraktivasi, Pengaruh Rasio Molar : Metanol - Nova Dwi Safitir; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is a renewable alternative fuel that can be made from vegetable oils. One was from the kapok seed oil by using an activated clay catalyst. The purpose of this study is to determine the characteristics of the clay catalysts for the synthesis of biodiesel, making biodiesel from kapok seed oil, determine the effect of the molar ratio of oil-methanol to yield biodiesel, and determines the physical properties and chemical properties of biodiesel produced. Activated clay as acids and bases using H2SO4 and NaOH. Biodiesel is made by reacting kapok seed oil and methanol at 60°C, the reaction time of 1.5 hours, and a catalyst concentration of 0.5% w/w. Treatment variations molar ratio of reactants affect the yield of biodiesel, as well as variations in the concentration of acids and bases for the activation of the catalyst on the clay affect the yield of biodiesel. The result of physical charactearization density 884 kg/m3, viscosity 3.28 mm2/s, acid number of 0.49 mg-KOH/g biodiesel and flash point 200°C meet the SNI standards (SNI 7182-2015).Keywords: activation, biodiesel, clay, molar ratio, yield